Inside Cover: Robust Colloidal Nanoparticles of Pyrrolopyrrole Cyanine J‐Aggregates with Bright Near‐Infrared Fluorescence in Aqueous Media: From Spectral Tailoring to Bioimaging Applications (Chem. Eur. J. 18/2017). Issue 18 (25th January 2017) - Yang, Cangjie; Wang, Xiaochen; Wang, Mingfeng; Xu, Keming; Xu, Chenjie
Abstract : Near‐infrared fluorescent J‐aggregates were discovered in colloidal nanoparticles of pyrrolopyrrole cyanines stabilized by amphiphilic block co‐polymers in aqueous media. The formation of such colloidal‐state J‐aggregates can be tuned by the chemical structure and the concentration of the chromophores inside the polymeric nanoparticles, and can be further enhanced by ultrasonic treatment. These J‐aggregate nanoparticles with an average diameter of 30 nm, exhibit a narrow emission band at 773 nm, a fluorescence quantum yield comparable to that of indocyanine green, and significantly enhanced photostability that is ideal for long‐term bioimaging. More information can be found in the Full Paper by M. Wang et al. onpage 4310 ff.